Quality and Adulteration in Ethnic Spices and Food Ingredients in Local Market - Sayali Harke; Ajit Pawar; Yojana Y Patil (Food, Agriculture and Natural Resources - NETWORKS, 2023)
The quality of Food depends on the nature of the ingredients used to prepare it, if the ingredient remains in best eminence without any adulteration then only we can get the pure quality food. This study aimed to detect the quality and adulterants in commonly used food ingredients and spices from local markets of Kolhapur city of India, which are usually used to prepare local ethnic food. Some tests from (the Food Safety and Standards Authority of India) are performed to check adulterants like insoluble impurities, chalk powder, washing soda, red lead salts, brick powder, and artificial colors in food ingredients. 5 sugar samples, 8 chili powder samples, 3 Jaggery samples, 6 turmeric powder samples, 6 common salt samples, 2 black pepper samples, 2 ghee or butter samples, 3 dal samples, 3 wheat flour samples, 2 honey samples, 2 cinnamon samples, and 3 coffee powder samples were analyzed. 2 chili, 1 black pepper, 1 cinnamon, 1 Jaggery 1 Honey, and 1 coffee powder samples are found with adulterants whereas most were without adulterants. Most of the local food ingredients are of good quality.